Eradication measures and products that inhibit in vitro mycelial growth of the fungus Neoscytalidium dimidiatum, the etiological agent of pitaya canker (Research, Society and Development, 2024)
The objective of this work was to identify the causal agent of the circular necrotic lesion present in cladodes and pitaya fruits, to test in vitro different products with potential fungicidal effect and to evaluate the effect of different eradicating products on infected pruned cladodes. Fruits and cladodes with symptoms of pitaya canker were analyzed using a magnifying glass and microscope. Isolation in PDA and inoculation was also carried out in healthy cladodes to observe symptoms. The isolated fungus was placed to grow in PDA culture medium previously mixed with the products; Castor oil, Prevam, Biometal copper, Kellus immune, Primecur, Kaumin, Bombardeiro, Serenade, Bordamil, Dithane, Bravonil, Mertin, Rovral, Sumilex, Mythos, Cantus, Fluazinam Nortox, Comet, Cercobin, Forum, Socre Flex, Cabrio Top, Orkestra, Opera, Nativo, Fusion, Tridium, Priori Xtra and Evolution. The products were applied to infected cladodes; Quaternary ammonia, Fortalece, Bordamil, Calda sulfocaucica all in concentrations of 5% and control with the objective of observing sporulation, spore germination and decomposition time. Pitaya cladodes and fruits presented stem canker caused by Neoscytalidium dimidiatum. The products; Prevam, Bordamil, Dithane, Mertin, Rovral, Sumilex, Fluazinam Nortox, Comet, Socre Flex, Cabrio Top, Orkestra, Opera, Nativo, Fusion, Tridium, Priori Xtra and Evolution at the doses tested completely inhibited the mycelial growth of the N. dimidiatum fungus. The products; Bordamil®, Sulfocaucic solution, Quaternary Ammonia and Fortalece® in concentrations of 5% accelerated the decomposition of the treated cladode and reduced the formation and germination of N. dimidiatum conidia.